La acreditación de la calidad de los estudios universitarios en el Perú - Ureña Peralta, Milbert (2011)
The peruvian university is included on the quality search word tendency. For such effect, "CONEAU" has designed quality models whose application is verified by the systemic and process approach which represent the principies of the total quality. The quality model has its own structure and conducts to the accred itation through the self and externa!evaluation.